Monitoring Wisconsin - Bender, Keith A. (My University, 2007)
In the Winter 2007 issue of Monitoring Wisconsin, the Institute for Survey and Policy Research (ISPR) of the University of Wisconsin- Milwaukee (UWM) presents a summary of work in progress on the older workforce in Wisconsin by Dr. Keith Bender of the UW-Milwaukee, Department of Economics.
Keywords: economics; wisconsin economy; aging workforce